LncRNA PTCSC3 inhibits cell proliferation in laryngeal squamous cell carcinoma by down-regulating lncRNA HOTAIR - Xiao, Dong (Biosci Rep, 2019)
It is known that lncRNA PTCSC3 inhibits thyroid cancer and glioma and STAT3 promotes cancer development. We, in the present study, investigated the potential involvement of PTCSC3 in laryngeal squamous cell carcinoma (LSCC) and explored its interactions with STAT3. In the present study, we showed that plasma PTCSC3 was down-regulated in early stage LSCC patients, and the down-regulation of PTCSC3 separated in early stage LSCC patients from control group. LncRNA HOTAIR was up-regulated in early stage LSCC patients and was significantly and inversely correlated with PTCSC3 in LSCC patients. PTCSC3 overexpression led to the inhibition of HOTAIR, while PTCSC3 expression was not significantly affected by HOTAIR overexpression. PTCSC3 overexpression mediated the inhibited, while HOTAIR overexpression mediated the promoted proliferation of LSCC cells. However, cell invasion and migration were not significantly affected by PTCSC3 overexpression. In addition, HOTAIR overexpression reduced the inhibitory effects of PTCSC3 overexpression on cancer cell proliferation. Moreover, PTCSC3 overexpression mediated the down-regulation of STAT3 and STAT3 overexpression mediated the up-regulation of HOTAIR. Therefore, PTCSC3 may negatively interact with HOTAIR through STAT3 to inhibit LSCC cell proliferation.